Analisis Kebutuhan Tenaga Rekam Medis Menggunakan Metode Workload Indicator Staff Needs (WISN) Di Unit Rekam Medis Puskesmas Langsat Pekanbaru: Analisis Kebutuhan Tenaga Rekam Medis Menggunakan Metode Workload Indicator Staff Needs (WISN) Di Unit Rekam Medis Puskesmas Langsat Pekanbaru - Natassa, Jihan; Maimun, Nur; Ulfa, Henny Maria; Wardani, Sri; Isnani, Rama (Jurnal Kesehatan Komunitas, 2024)
Human Resources is an important component of an institution which acts as a thinker and planner for the development of an institution. Every institution needs to analyze and identify the availability of human resources to achieve its goals. One way is by mapping the workload. Patient visits to the Langsat health centre are 35-40 people/day. There are 2 medical records officers, none of whom have a D3 Medical Records education. This research aims to determine the estimated number of medical records personnel using the WISN method. This research uses a qualitative descriptive research design with the time and motion study method. The research informants were 2 medical records officers and 1 TU head. Data were collected using observation table instruments, interviews, stopwatches and computers and then analyzed using the WISN method. When the research was carried out in August 2023. The variables of this research were available working time, workload standards, allowance standards, and the number of workers needed. The research results are the amount of available working time is 69,360 minutes/year, the workload standard is 180,336 minutes/year, the allowance standard is 15,480 minutes/year or 0.22, and the workforce requirement is 3 people. From the results of the workforce calculation, it is hoped that there will be an additional 1 person on staff, especially D3 Medical Records staff.